Risk classification in primary prevention of CVD according to QRISK2 and JBS3 'heart age', and prevalence of elevated high-sensitivity C reactive protein in the UK cohort of the EURIKA study. Issue 2 (17th November 2018) - Johns, Ieuan; Moschonas, Konstantinos E; Medina, Jesús; Ossei-Gerning, Nicholas; Kassianos, George; Halcox, Julian P
Abstract : Objectives: This study assessed cardiovascular disease (CVD) risk classification according to QRISK2, JBS3 'heart age' and the prevalence of elevated high-sensitivity C reactive protein (hsCRP) in UK primary prevention patients. Method: The European Study on Cardiovascular Prevention and Management in Usual Daily Practice (EURIKA) (NCT00882336 ) was a cross-sectional study conducted in 12 European countries. 673 UK outpatients aged ≥50 years, without clinical CVD but with at least one conventional CVD risk factor, were recruited. 10-year CVD risk was calculated using QRISK2. JBS3 'heart age' and hsCRP level were assessed according to risk category. Results: QRISK2 and JBS3 heart age was calculated for 285 of the 305 patients free from diabetes mellitus and not receiving a statin. QRISK2 classified 28%, 39% and 33% of patients as low (<10%), intermediate (10% to <20%) and high (≥20%) risk, respectively. Two-thirds of low-risk patients and half of intermediate-risk patients had a heart age ≥ 5 years and ≥ 10 years higher than their chronological age, respectively. Half of low-risk patients had hsCRP levels ≥2 mg/L and approximately 40% had levels ≥3 mg/L. Approximately 80% of low-risk patients had both elevated hsCRP and heart age relative to their chronological age. Conclusions: Almost 40% more patients in this 'at risk' group would be eligible for statin therapy following the lowering of the National Institute for Health and Care Excellence treatment threshold to ≥10% 10-year risk. Of patients falling below this treatment threshold, almost all were at increased lifetime risk as measured by JBS3, and of these, the majority had elevated hsCRP levels. These patients with high absolute risk may benefit from early primary CVD prevention.